Assessment of cataloging services in an academic library. Issue 1 (2nd January 2016) - Sassen, Catherine; Welch, Rebecca; Loafman, Kathryn
Abstract : Personnel in Public Services and in Cataloging and Metadata Services were surveyed to determine how they rated the importance of various cataloging services, and to gauge their satisfaction with these services. The two groups differed in the importance and satisfaction scores that they assigned to certain cataloging services. The issues raised by respondents suggested that Cataloging and Metadata Services should take a more proactive approach to communication with Public Services and indicated the need for further research.